Anemia of Chronic Disease in Ankylosing Spondylitis: Improvement Following Anti-TNF Therapy - Ki-Jo KIM; Chul-Soo CHO (Archives of Rheumatology, 2012)
Objectives: We assessed the prevalence of anemia at the initiation time of anti-tumor necrosis factor (anti-TNF) therapy and the change of hemoglobin level following anti-TNF therapy in ankylosing spondylitis (AS). Patients and methods: Forty-three patients with AS, who received anti-TNF agents, were retrospectively analyzed in the study. Hemoglobin, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), ferritin, and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores were evaluated at baseline and at 32 weeks following anti- TNF therapy. Anemia was defined as a hemoglobin level <12 mg/dL for women and <13 mg/dL for men. Serum ferritin ≥60 ng/ml suggested anemia of chronic disease, whereas ferritin <60 ng/ml suggested iron deficiency anemia (IDA). Results: Anemia was found in 12 of 43 (27.9%) AS patients at baseline. Four of 12 anemic patients indicated anemia of chronic disease (33.3%), whereas eight indicated IDA (66.7%). At 32 months following anti-TNF therapy, the mean hemoglobin level was improved (from 13.8±1.7 to 14.3±1.6 mg/dl, p=0.001) along with decline of ESR, CRP, and BASDAI (all, p<0.001). Improvement of hemoglobin level showed positive correlation with the change of ESR and CRP (r=0.608, p<0.001 and r=0.588, p<0.001, respectively). In multivariate analysis, the change of ESR and CRP were associated independently with improvement of hemoglobin level. Recovery from anemia was significant in patients with anemia of chronic disease (p=0.01), whereas not significant in patients with IDA (p=0.079). Conclusion: Anemia is not uncommon in AS patients. Improvement of hemoglobin level is observed with effective treatments in patients with AS. Anti-TNF therapy is more effective with improvement of hemoglobin than diseasemodifying antirheumatic drugs (DMARDs), especially in patients with anemia of chronic disease.